2014
DOI: 10.1371/journal.pone.0096718
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 Inhibits Tumor Metastasis and Reverses Epithelial-Mesenchymal Transition through AKT/ERK1/2 Inactivation by Targeting EGFR in Epithelial Ovarian Cancer

Abstract: Epidermal growth factor receptor (EGFR) overexpression and activation result in increased proliferation and migration of solid tumors including ovarian cancer. In recent years, mounting evidence indicates that EGFR is a direct and functional target of miR-7. In this study, we found that miR-7 expression was significantly downregulated in highly metastatic epithelial ovarian cancer (EOC) cell lines and metastatic tissues, whereas the expression of, EGFR correlated positively with metastasis in both EOC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 42 publications
2
64
0
1
Order By: Relevance
“…There exists precedent for modulating EMT through the suppression of EGFR. Zhou et al (2014) showed that suppression of EGFR by miRNA-7 is able to inactivate the ERK-1/2/ATK signaling cascade, thus reversing EMT and attenuating metastasis in epithelial ovarian cancer cells. Zuo et al (2011) found that EGFR activation can induce EMT-like phenotype change and MMP-9-mediated degradation of E-cadherin in HNSCC SCC10A cells through the ERK-1/2 and PI3K signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There exists precedent for modulating EMT through the suppression of EGFR. Zhou et al (2014) showed that suppression of EGFR by miRNA-7 is able to inactivate the ERK-1/2/ATK signaling cascade, thus reversing EMT and attenuating metastasis in epithelial ovarian cancer cells. Zuo et al (2011) found that EGFR activation can induce EMT-like phenotype change and MMP-9-mediated degradation of E-cadherin in HNSCC SCC10A cells through the ERK-1/2 and PI3K signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-7 also suppresses the effector of EGFR signaling by inactivating protein kinase B (PKB/Akt) and extracellular signal-regulated kinase 1/2 (ERK1/2). [43][44][45] Therefore, the regulatory function of circRNAs via their influence on miR-7 is clear: overexpression of ciRS-7 could act as a microRNA sponge to restrain the expression miR-7 and therefore elevate EGFR expression. EGFR overexpression is associated with disease advancement, resistance to chemotherapy and radiation therapy, and poor prognosis, and is closely observed in a series of solid tumors, including cancer stem-like cells (CSC), gastric cancer, hepatocellular carcinoma and colorectal carcinoma.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…48 In hepatocellular carcinoma (HCC), miR-7 is decreased in HCC cell plasma and several studies have confirmed its outstanding role in cell cycle regulation. [42][43][44] MiR-7 directly silences the cyclin E1 (CCNE1) gene, and CCNE1 forms a complex with and functions as a regulatory subunit of CDK2, which is required for G1 to S transition. 49 Therefore, the overexpression of miR-7 arrests the cell cycle in HCC.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…Also, miR-7 is expressed abundantly in human pancreas and endocrine cells and has a specific role in endocrine cell differentiation and function [10] . It has been demonstrated that miR-7 is a tumor suppressor in breast, lung and ovarian cancers, and glioblastoma, mainly focusing on its relationship with EGFR [11][12][13][14][15] . Accumulating evidence shows that miR-7 can simultaneously target a variety of mRNAs involved in diverse signaling pathways in different tumors.…”
Section: Introductionmentioning
confidence: 99%